ANALISIS STRUKTUR MODAL, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP NILAI SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Idayanti, Rini; Hasni, Hasni (Islamic Banking and Finance, 2022)
Stock value or stock price can be interpreted as a price that is created from the interaction of buyers and sellers stock, which based on their expectations for corporate profits. High value of the stock would make the company's value also high. There are several factor that affect the stock value, in this study only examined three variables, which are the Capital Structure, Profitability and Size Company. The study aims to determine the Capital Structure, Profitability and Size Company simultaneously and partially influence the stock value of Manufacture companies listed in Stock Exchange on period of 2016-2018. 36 companies was analyzed as the samples. The analytical method used was multiple linear regression analysis using eviews program. The results showed that simultaneous Capital Structure, Profitability,size company influence on Stocks value. Capital Structureand and profitability partially affect the stock value, while size copany Policy does not affect the stock value. Suggestions for company management, must maintain the state of the company's capital structure and efficiently, so that company is able to perform an optimal capital structure.